More Terminological Blunders - Braude, Stephen (Journal of Scientific Exploration, 2020)
In my previous Editorial, I took a short detour from the main topic (telepathy and mental privacy) to comment briefly on one of the deeper flaws in the trendy, but seriously misguided, practice of replacing the terms “ESP” and “PK” with (respectively) “anomalous cognition” and “anomalous perturbation.” As I’ve discussed in great detail elsewhere (Braude, 2020), there’s actually quite a lot that’s wrong with this terminological folly. And it’s hardly the only time psi researchers have botched efforts to explicate or replace some of the field’s key concepts. The terminological error that I discussed in my earlier Editorial was the failure to accommodate the valuable distinction between ESP-cognition and ESP-interaction. And in that Editorial, I also noted that another, and increasingly trendy, practice likewise commits this error. It’s the strategy of abandoning the venerable arsenal of psi-terms and replacing them with a single expression—either “nonlocal awareness” or “nonlocal consciousness.” (The underlying rationale for this is usually that the traditional vocabulary is likely to be professionally toxic.) I’m thinking about these matters again because recent events have conspired to remind me of still another, but less trendy and prevalent, approach to parapsychological terminology that also deserves a few words of disapproval.